Secondary central nervous system relapse in diffuse large B cell lymphoma in a resource limited country: result from the Thailand nationwide multi-institutional registry - Kitsada Wudhikarn (2018)
© 2016, Springer-Verlag Berlin Heidelberg. Secondary central nervous system (CNS) relapse is a serious and fatal complication of diffuse large B cell lymphoma (DLBCL). Data on secondary CNS (SCNS) relapse were mostly obtained from western countries with limited data from developing countries. We analyzed the data of 2034 newly diagnosed DLBCL patients enrolled into the multi-center registry under Thai Lymphoma Study Group from setting. The incidence, September 2006 to December 2013 to represent outcome from a resource limited pattern, management, and outcome of SCNS relapse were described. The 2-year cumulative incidence (CI) of SCNS relapse was 2.7 %. A total of 729, 1024, and 281 patients were classified as low-, intermediate-, and high-risk CNS international prognostic index (CNS-IPI) with corresponding 2-year CI of SCNS relapse of 1.5, 3.1, and 4.6 %, respectively (p < 0.001). Univariate analysis demonstrated advance stage disease, poor performance status, elevated lactate dehydrogenase, presence of B symptoms, more than one extranodal organ involvement, high IPI, and high CNS-IPI group as predictive factors for SCNS relapse. Rituximab exposure and intrathecal chemoprophylaxis offered no protective effect against SCNS relapse. At the time of analysis, six patients were alive. Median OS in SCNS relapsed patients was significantly shorter than relapsed patients without CNS involvement (13.2 vs 22.6 months) (p < 0.001). Primary causes of death were progressive disease (n = 35, 63.6 %) and infection (n = 9, 16.7 %). In conclusion, although the incidence of SCNS relapse in our cohort was low, the prognosis was dismal. Prophylaxis for SCNS involvement was underused even in high-risk patients. Novel approaches for SCNS relapse prophylaxis and managements are warranted.